1997
DOI: 10.1007/bf02446849
|View full text |Cite
|
Sign up to set email alerts
|

The significance of enzymuria in assessing the nephrotoxicity of antitumor chemotherapy in children

Abstract: The significance of enzymuria in assessing the nephrotoxicity of cisplatin in a total dose of 100 mg/m 2 or iphosphamide in a total dose of 9 g/m 2 for children with solid malignant tumors (10 and 9 patients, respectively) was studied. Chemotherapy caused stable hyperenzymuria consisting in a significant increase in N-acetyl-lS-D-hexosaminidase, 7-glutamyltransferase, and alanine aminopeptidase activities in the urine during chelnotherapy in comparison with the initial values. The levels of enzyme excretion wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…It is worth noting that HEX activity in the urine of children with early-stage diabetic nephropathy is 2-fold higher compared to healthy children (35) . Liubimova et al found HEX to be a more sensitive marker of cytotoxic drug-induced renal tubular damage than urea or albumin/creatinine ratio (36,37) . Urinary activity of HEX may help assess therapeutic outcomes in alcoholism (38) .…”
Section: Lysosomementioning
confidence: 99%
“…It is worth noting that HEX activity in the urine of children with early-stage diabetic nephropathy is 2-fold higher compared to healthy children (35) . Liubimova et al found HEX to be a more sensitive marker of cytotoxic drug-induced renal tubular damage than urea or albumin/creatinine ratio (36,37) . Urinary activity of HEX may help assess therapeutic outcomes in alcoholism (38) .…”
Section: Lysosomementioning
confidence: 99%
“…In this regard, the search for the most accurate biomarkers that would allow for early diagnosis of CKD and establishing the cause of its development is of current concern. At the moment, a number of biomarkers associated with nephrotoxicity are known, but FDA (Food and Drug Administration) and EMEA (European Medicines Agency) have approved only KIM-1 (kidney injury molecule-1), albumin, total protein, β 2-microglobulin, cystatin C, clusterin, and TFF3 (trefoil factor 3) for routine use in practice [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, these studies deal with the problem of early hydronephrotic transformation of the kidney [7,25], mechanisms of development of chronic and acute renal insufficiency [4,14,18], and the problem of nephrotoxic lesions caused by chemotherapy of malignant tumors [13,20,24,30,321.…”
mentioning
confidence: 99%
“…This is a very considerable burden on the urinary system. Therefore, dysfunctions of the urinary system should be detected and corrected before applying intense oncological therapy [13,20,24,30,32,33].…”
mentioning
confidence: 99%